The Role of Village Apparatus to Prevent Early Marriage in Indonesia - Dariyo, Agoes; Tumanggor, Raja Oloan (UIN Sunan Kudus, 2022)
ABSTRACTVillage officials (village heads, hamlet heads, village secretaries, village staff) have a strategic role to prevent early marriage in Indonesia. This study uses a qualitative approach with data collection techniques, namely structured interviews based on a question guide. The research subjects involved 9 people consisting of 4 village heads, 4 hamlet heads and 1 village staff. Data analysis techniques using thematic approach (thematic approach) and by using the concept of Urrie Broffenbrenner's ecological systems theory. The results of the study can be concluded that they as village officials can take practical steps, namely; (1) socializing law number 1 of 1974 concerning the minimum age for marriage is 19 years, (2) preventing (forbidding, hindering or hindering) marriage before reaching the age of 19 years, (3) encouraging citizens to participate in compulsory 12 years of education, (4) serving the provision of certificates for residents who take care of marriage dispensation letters, (5) providing special policies for residents to get married immediately, because they were pregnant before marriage. Furthermore, after doing these things, it was also found that (1) the village community has the awareness to marry at least 19 years old, (2) the community has the awareness to improve education, and, (3) the community has the awareness to avoid promiscuity. All the results of this study can be seen in this paper. Key words: village apparatus, preventing early marriage. ABSTRAKAparatur desa (kepala desa, kepala dusun, sekretaris desa, staf desa) memiliki peran strategis untuk mencegah perkawinan usia dini di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengambilan data yaitu wawancara terstruktur yang didasarkan pada panduan pertanyaan. Subyek penelitian melibatkan 9 orang yang terdiri dari 4 kepala desa, 4 kepala dusun dan 1 staf desa. Teknik analisis data dengan menggunakan pendekatan tematik (thematic approach). Hasil penelitian dapat disimpulkan bahwa mereka sebagai aparatur desa dapat melakukan langkah-langkah praktis yaitu; (1) melakukan sosialisasi undang-undang nomor 1 tahun 1974 mengenai usia minimal menikah adalah 19 tahun, (2) mencegah (melarang, menghambat atau menghalangi) pernikahan sebelum mencapai usia 19 tahun, (3) mendorong warga untuk ikut wajib belajar 12 tahun, (4) melayani penyediaan surat keterangan bagi warga yang mengurus surat dispensasi nikah, (5) memberikan kebijakan khusus bagi warga untuk segera menikah, karena mereka sudah hamil sebelum menikah. Selanjutnya, setelah melakukan hal-hal tersebut, maka ditemukan pula bahwa (1) masyarakat desa memiliki kesadaran untuk menikah minimal usia 19 tahun, (2) masyarakat memiliki kesadaran untuk meningkatkan pendidikan, dan, (3) masyarakat memiliki kesadaran untuk menghindari pergaulan bebas. Semua hasil penelitian ini dapat dilihat dalam tulisan ini. Kata-kata kunci: aparatur desa, mencegah perkawinan usia dini.